Ecophysiological aspects of fruit crops in the era of climate change. A review (2016)
The increased concentration of carbon dioxide (CO2) and other greenhouse effect gases has led to global warming, which has resulted in climate change, increased levels of ultraviolet (UV) radiation and changes in the hydrological cycle, affecting the growth, development, production and quality of fruit crops, which undoubtedly will be difficult to predict and generalize because the physiological processes of plants are multidimensional. This review outlines how the effects of high/low solar radiation, temperature, water stress from droughts, flooding and rising levels of CO2 in the atmosphere affect fruit crops and their growth and physiology.